Social work with disabilities in Kazakhstan (Herald of Journalism, 2020)
Since the attainment of independence, in social policy ok Kazakhstan the great importance was given to fostering a system of social protection of people with disabilities. The national policy, towards of persons with disabilities in the Republic of Kazakhstan has been. Reflected in the regula- tory and legal acts and conceptual documents. In recent years Kazakhstan has drastic measures to improve the lives of persons with disabilities. The author indicates that the various forms of social assistance on the part of the state. In our days in the various forms of social assistance on the part of the state. In our days in the republic actively developing the system chari- table assistance to disabled persons and to those in need. In this article there are concrete examples of activities of non-governmental organiza- tions in solving the problems of people with disabilities.
Keywords: disabilities, declaration, rampant, hospital, patient.